Pharmacological Approaches in an Experimental Model of Non-Small Cell Lung Cancer: Effects on Tumor Biology - Mateu-Jimenez, Mercè (2016)
Lung cancer (LC) remains the leading cause of cancer mortality worldwide, and non-small cell LC (NSCLC) represents 80% of all LC. Oxidative stress and inflammation, autophagy, ubiquitin-proteasome system, nuclear factor (NF)-KB, and mitogen activated protein kinases (MAPK) participate in LC pathophysiology. Currently available treatment for LC is limited and in vivo models are lacking. We hypothesized that antioxidants and NF-KB, MAPK, and proteasome inhibitors may exert an antitumoral response through attenuation of several key biological mechanisms that promote tumorigenesis and cancer cell growth. Body and tumor weights, oxidative stress, antioxidants, inflammation, NF-KB p65 expression, fibulins, apoptosis, autophagy, tumor and stroma histology were evaluated in the subcutaneous tumor of LC (LP07) adenocarcinoma) BALB/c mice, with and without concomitant treatment with NF-KB (sulfasalazine), MEK (U0126), and proteasome (bortezomib) inhibitors, and N-acetyl cysteine (NAC). Compared to LC control mice, in subcutaneous tumors, the four pharmacological agents reduced oxidative stress markers and tumor proliferation (ki-67). Inflammation and NF-KB p65 expression were attenuated by NF-KB and MAPK inhibitors, and the latter also enhanced apoptotic markers. Catalase was induced by the three inhibitors, while bortezomib also promoted superoxide dismutase expression. NF-KB and MEK inhibitors significantly reduced tumor burden through several biological mechanisms that favored tumor degradation and attenuated tumor proliferation. These two pharmacological agents may enhance the anti-tumor activity of selectively targeted therapeutic strategies for LC. Proteasomal inhibition using bortezomib rather promotes tumor degradation, while treatment with antioxidants cannot be recommended. This experimental model supports the use of adjuvant drugs for the improvement of LC treatment.